INFLUENCE OF FRICTION SURFACES PROPERTIES OF COMPOSITE MATERIALS ON ACOUSTIC EMISSION - Filonenko, Sergiy; Kosmach, Oleksandr (Proceedings of National Aviation University (archive), 2013)
The simulation of amplitude and energy of acoustic emission resulting signals at friction of composite materials surfaces layers was conducted. The regularities of changes in the amplitude and energy parameters of acoustic emission resulting signals which are depending from hardness of composite materials surfaces layers were determined. The description of regularities of changes with their statistical estimates was conducted.